Influence of perinatal and other factors in the aetiology of Molar Incisor Hypomineralisation/ Rohaida Abdul Halim, Bernadette K Drummond and W Murray Thomson - Abdul Halim, Rohaida; Drummond, Bernadette K; Thomson, W Murray (UiTM Press, 2019)
Objective: The aims of this study were to compare associations between dental health and pregnancy circumstances, birth history and early childhood health in children with and without Molar-Incisor Hypomineralisation (MIH). Methods: A matched case-control (n=101) study investigated perinatal and early childhood factors that could be associated with development of MIH. Case group (n=46) children (with MIH) were identified from the University of Otago Paediatric Dentistry Clinic. Control group (n=55) children (matched for age and gender, and with no signs of MIH) were selected from another clinic. Clinical examination recorded dental enamel defects and caries status. Pregnancy history and the child's development and medical history were recorded by questionnaire. Mothers and children's birth records were examined. Results: There were no significant socio-demographic differences between case or control groups. Children diagnosed with MIH had more problems at birth, including oxygen deprivation, one or more signs of foetal distress, premature birth or low birth weight. More mothers of MIH children had received drugs during delivery, including nitrous oxide, pethidine, or antibiotics. Conclusion: In this study, premature birth was found to be significantly associated with the occurrence of MIH.